Waste Analysis Using Value Stream Mapping (Vsm) and Fmea in the Implementation of Lean Manufacturing on the Woven Bag Production Line at PT. Kerta Rajasa Raya - Yekti Condro Winursito; Dewi Mardiana Aditya; Joumil Aidil Saifuddin (SAINTIS Publishing, 2026)
This research aims to analyze and reduce waste in the woven bag production line at PT Kerta Rajasa Raya through the Lean Manufacturing approach using the Value Stream Mapping (VSM) and Failure Mode and Effect Analysis (FMEA) methods. The company experienced various types of waste such as waiting time, unnecessary movement, over-processing, and product defects, which led to a decrease in production efficiency. The analysis results showed that the highest types of waste were unnecessary motion, defects, and excess processing. Using VSM, it was found that of the total production time of 51,997 seconds, only 51.1% were value-added activities. Through the application of FMEA, the main causes of waste were identified based on the highest Risk Priority Number (RPN) value, and a number of improvement recommendations were designed such as improving work layout, implementing quality gate, and strengthening preventive maintenance. After the improvement, production time was reduced to 42,139 seconds and process cycle efficiency increased to 63.1%. These results show that the application of Lean Manufacturing through VSM and FMEA is effective in improving production efficiency and reducing waste in the company.